Pengembangan Fussion Food pada Kue Talam Ebi sebagai Modifikasi Makanan Tradisional - Bridha, Risya Ladiva; Priatini, Woro; Hamdani, Zahratul Insaniyah (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2023)
This research was motivated by the decline in public interest in traditional foods. Kue talam is one of the traditional Indonesian foods that is currently included in the less popular category. This research aims to increase the attractiveness of traditional food by creating a modified kue talam product that will be combined with other foods, this is known as fusion. The research method used by researchers is quantitative research with experimental methods. The experimental planning carried out is using a Randomized Group Design (RAK). To test the recipe standard and product quality using the o test and consumer acceptance test. The number of samples used in this study were 15 trained and somewhat trained panelists who would test four product samples, including; 1) Steamed Ebi Talam with Puff Pastry (TEKPP); 2) Baked Ebi Talam with Puff Pastry (BTEPP). Organoleptic test results obtained from 15 trained and moderately trained panelists resulted in TEKPP products as the most preferred products. Furthermore, TEKPP products will be tested on 100 consumer panelists to determine the acceptability of the modified product, and the results obtained are that the product falls into the category of very like, so it can be concluded that the modified product can be accepted by consumers. The results of the hypothesis test on the product there is an effect of modification on the attractiveness of traditional food on Kue Talam Ebi products.